1986
DOI: 10.1192/bjp.149.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Witchcraft and Psychotherapy

Abstract: Belief in witchcraft, which serves a variety of social functions and personal defences, is bound to emerge in psychotherapy with individuals from a culture that holds such beliefs; endeavouring to understand it can open up new therapeutic possibilities. The nature of witchcraft, the profiles with which it intrudes into therapy, and the socio-psychological functions it fulfills are considered. Referring such patients to witchdoctors is morally unjustifiable, but the witch-doctor's folk-image provides a floating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In clinical practice a few decades ago, Neki et al. (, ) observed that African patients had varying expectations from psychiatrists in comparison with shamans who offered traditional healing practices. In African cultures, there was a clearly observed discrepancy between the African illness and expectations from European clinicians.…”
Section: Placebo Responsementioning
confidence: 99%
“…In clinical practice a few decades ago, Neki et al. (, ) observed that African patients had varying expectations from psychiatrists in comparison with shamans who offered traditional healing practices. In African cultures, there was a clearly observed discrepancy between the African illness and expectations from European clinicians.…”
Section: Placebo Responsementioning
confidence: 99%
“…It became apparent that being mad or having a mad person in the family was a practical problem that required decisions about how to view the problem and where to turn for help. Edgcrton (1966) and Neki et al (1986) expressed similar ideas saying that the clinician or researcher must ask both "How did the illness come about?" While those interviews were being conducted on a daily basis, I sought other avenues for learning about the Zanzibari view of madness, the spirit world, the curative use of the Koran and other forms of traditional treatment.…”
Section: Had Planned To Administer the Schroeder-block-campbell (Sbc)mentioning
confidence: 99%
“…Neki (1973) suggested that the suitable paradigm for indian patient is 'Guru-Chela relationship'. In his later article on witchcraft and psychiatry (Neki et al, 1986), he recommended strategic treatment. In a nutshell what we call as commonsense psychotherapy.…”
Section: Which Psychotherapy T O O F F E R ?mentioning
confidence: 99%